2014
DOI: 10.3748/wjg.v20.i8.1951
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer and lymph nodes: The obsession with the number 12

Abstract: Lymphadenectomy of colorectal cancer is a decisive factor for the prognostic and therapeutic staging of the patient. For over 15 years, we have asked ourselves if the minimum number of 12 examined lymph nodes (LNs) was sufficient for the prevention of understaging. The debate is certainly still open if we consider that a limit of 12 LNs is still not the gold standard mainly because the research methodology of the first studies has been criticized. Moreover many authors report that to date both in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 110 publications
4
81
0
1
Order By: Relevance
“…This number, though in the context of an issue still unresolved, 36 has been considered the minimum for a correct staging of the tumor. Currently data similar to ours has been reported in literature if it is true that in the US reports published between 2005 and 2010 revealed that lymphadenectomy was still considered inadequate in 48 to 63% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…This number, though in the context of an issue still unresolved, 36 has been considered the minimum for a correct staging of the tumor. Currently data similar to ours has been reported in literature if it is true that in the US reports published between 2005 and 2010 revealed that lymphadenectomy was still considered inadequate in 48 to 63% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…16 The number of positive nodes is dependent on the number of nodes dissected and the extent of resection of nodes as well as the location of the lesion.Lesions retrieved in the right side of colon are more commonly associated with a high frequency of positive nodes. 17,18 The dissection of 12 nodes is regarded as adequate for staging colorectal cancer, however, there is a controversy regarding whether this numberis inadequate lead to arisk of understaging.…”
Section: Discussionmentioning
confidence: 99%
“…It was similar to other studies where the retrieved nodes ranges from 10 to 26.8 nodes, which signifies the adequacy of nodal dissection in our study. 10,18 The cut off LNR has been reported to be 0.12 to 0.35. 10 In our series, the mean LNR was 0.31 in the younger patients where as in those above 40 years, it was 0.13 and the difference was statistically significant.…”
mentioning
confidence: 99%
“…In recent population studies conducted in the USA and Europe, it has been reported that the ''magic'' number of 12 lymph nodes examined is rarely achieved in district or community hospitals which fail to hit the target in 33-60 % of the cases [115][116][117][118]. The national report card concluded that only the Comprehensive Cancer Centers were compliant with 92 % of patients with more than 12 lymph nodes retrieved, thus stressing the importance of a multidisciplinary team (MDT) approach and of developing of pooled experience [119].…”
Section: Lymph Node Harvestingmentioning
confidence: 99%